Electronics engineers' handbook - Fink, Donald G. (McGraw-Hill, 1975)
It features two new sections, one covering microsensors and the other detailing the many organizations pertinent to electronics engineering. There is material on digital computing, measurement and control circuits, computer-aided design, reliability, lasers and optoelectronics, video, audio and telecommunications.